FORMATION OF AN INFORMATION AND CONSULTING CONTROL SYSTEM OF REGIONAL AGRARIAN AND INDUSTRIAL COMPLEX - T. Sozaeva; A. Hitieva (Вестник университета)
Modern regional economies in many respects is defined by interaction and interference of regularities of global, national and regional levels. In the article an attempt of formation of an information and consulting control system of regional agrarian and industrial complex which has to provide high competitiveness and a sustainable development of territories is made.